Why Don’t We See Poverty Convergence? - Ravallion, Martin (2012)
We are not seeing faster progress against poverty amongst the poorest developing countries. Yet this is implied by widely accepted "stylized facts" about the development process. The paper tries to explain what is missing from those stylized facts. Consistently with models of economic growth incorporating borrowing constraints, the analysis of a new data set for 100 developing countries reveals an adverse effect on consumption growth of high initial poverty incidence at a given initial mean. A high incidence of poverty also entails a lower subsequent rate of progress against poverty at any given growth rate (and poor countries tend to experience less steep increases in poverty during recessions). Thus, for many poor countries, the growth advantage of starting out with a low mean ("conditional convergence") is lost due to their high poverty rates. The size of the middle class--measured by developing-country, not Western, standards--appears to be an important channel linking current poverty to subsequent growth and poverty reduction. However, high current inequality is only a handicap if it entails a high incidence of poverty relative to mean consumption.